Former Yugoslav Republic of Macedonia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper and Statistical Appendix sheds light on the Former Yugoslav Republic (FYR) of Macedonia's low growth and high unemployment during the 1990s by analyzing enterprise level data. The paper provides some background information on FYR Macedonia's enterprise sector. It presents an assessment of enterprise sector developments during the 1990s, including the extent of firm entrance and exit. The paper also describes the results of an econometric study that examines the factors that have facilitated restructuring in surviving firms since FYR Macedonia's independence in September 1991.